Development of Athletic Equipment Modifications In PJOK Learning Elementary School: Development of Athletic Equipment Modifications In PJOK Learning Elementary School - Rinaldi Aditya; Boby Helmi; Khairul Usman (Journal of Midwifery and Nursing, 2020)
The standard of athletic equipment is highly unlikely when given at elementary school age students, because for posture and weight load capability is still not feasible in primary school learning process. Priority in particular learning materials is to introduce fine athletics and to ensure that students can do tenik and style right in the motion of each number atletik.Tujuan modification athletic equipment development research is to train teachers to make modifications in learning skilled PJOK particularly athletic material with material easy to find, easy to be processed in a simple, practical, and economical, so it is very appropriate to be used by all the schools, especially primary schools.